A comparative study of Avicenna's and Ghazali's views on God's attributes - farideh hakimi; Mahdi Dehbashi (پژوهش‌نامه کلام تطبیقی شیعه, 2023)
The main purpose of this research is to examine the views of Ghazali and Ibn Sina on one of the most controversial theological issues in the field of Islamic philosophy, namely the attributes of God and how these two thinkers explain the divine attributes. Due to the fact that Ibn Sina considers it impossible to understand the nature of God, therefore, he considers it possible to know him only through the knowledge of divine attributes.Because Ibn Sina considers God's attributes to be the same as His essence, so whoever can know His attributes is as if he has understood His essence. Contrary to Ibn Sina's opinion, Ghazali's approach regarding God's attributes has undergone many changes during different stages of his life. Because according to him, we can only attribute attributes to God that God has described Himself to. So, based on this, he considers God's attributes neither as his nor as other than him, and he believes that we should not ask any questions about this at all. The present article analyzed this issue with a library method and sought to resolve the ambiguities raised in this regard